Descemet Membrane Endothelial Keratoplasty After Failed Descemet Stripping Without Endothelial Keratoplasty. Issue 7 (July 2017) - Rao, Rohini; Borkar, Durga S.; Colby, Kathryn A.; Veldman, Peter B.
Abstract : Purpose: To describe the clinical course, surgical experience, and postoperative outcomes of 3 patients with Fuchs endothelial dystrophy who underwent Descemet membrane endothelial keratoplasty (DMEK) after failed Descemet stripping without endothelial keratoplasty. Methods: Three patients who underwent DMEK for management of persistent corneal edema after deliberate Descemet stripping in the setting of Fuchs endothelial dystrophy were identified. Patients were examined at day 1, week 1, and months 1, 3, and 6 after DMEK. Visual acuity, central corneal thickness (CCT), and evaluation of central corneal endothelial cell counts were recorded. Results: Two women and one man, aged 56, 72, and 68 years, were included. The time interval between primary Descemet stripping and DMEK ranged from 3.5 to 8 months. Preoperative visual acuities were 20/200, 20/300, and 20/80. Immediately before DMEK, no patients had countable central endothelial cells, and CCTs were 825, 1034, and 878 μm. After DMEK, all patients had improvement in visual acuity to 20/70, 20/20, and 20/20 with CCTs of 529, 504, and 528. The postoperative period in the first case was notable for the immediate development of a pigmented pupillary membrane with posterior synechiae, as well as cystoid macular edema, of uncertain chronicity, noted 1 month postoperatively. The second case also developed posterior synechiae. Two cases completed 6-month endothelial cell counts totaling 2200 and 3114 cells per square millimeter (endothelial cell loss of 13% and 5.3%). Conclusions: DMEK is a reliable procedure to facilitate corneal rehabilitation and visual recovery in the event of poor corneal clearance after Descemet stripping without endothelial keratoplasty.